Relationship between Process of Care and Subsequent Increase in Damage in SLE - Yelin, Edward (Arthritis Care Res (Hoboken), 2017)
OBJECTIVES: The present study evaluates whether low ratings of interactions with providers and health plans in 2013 were associated with increased SLE damage in 2015. METHODS: Data derive from the Lupus Outcomes Study (LOS) annual surveys and include items from the Consumer Assessment of Health Plans and Interpersonal Processes of Care Scale measuring dimensions of health care interactions. We use ordinary least squares regression to model the change in disease damage over a two-year period, 2013-2015, as a function of ratings of multiple dimensions of interactions with providers and health plans, with and without adjustment for demographic characteristics, socioeconomic status, and SLE and overall health status, and logistic regression to estimate the effect of the same matrix of variables on the probability of experiencing a minimal clinically important increase in damage. RESULTS: There were 566 LOS respondents who were followed from 2013-2015 and who rated their providers and health plans in 2013. After adjustment, persons with SLE rating their providers poorly in patient-provider communication experienced a significantly greater accrual of disease damage (0.23, 95% CI 0.09, 0.38) and were more likely to experience a minimal clinically important increase in damage (OR 2.35, 95%CI 1.25, 4.39). After adjustment, those rating their health plan poorly on care coordination experienced a significantly greater accrual of disease damage (0.19, 95%CI 0.03, 0.35) and were more likely to experience a minimal clinically important increase in damage (OR 2.20, 95%CI 1.12, 4.34). CONCLUSIONS: Poor patient-provider communication and care coordination may result in increased disease damage.